GAMBARAN MOTIVASI KERJA GURU SEKOLAH LUAR BIASA X - BEATITUDO, EWALDUS SENARAI; DEWI, FRANSISCA IRIANI R (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2024)
Special School X is a school that provides learning and development space for children with special needs. SLB X, which has been established for more than 25 years, has several branches. The aim of this research is to find out the overview of the work motivation of teachers of special school students at special school X. The method used in this research is mixed methods with a quantitative preliminary type of design. The researcher collects quantitative data, then create a questionnaire, then seeking for participants to explore further through interviews regarding work motivation variable. Quantitative surveys or questionnaires provide a general description, qualitative interviews will provide further descriptions of work motivation. Quantitative surveys or questionnaires provide a general description, qualitative interviews will provide further descriptions of work motivation. This research involved 34 teacher participants consisting of 14 men and 20 women. Data was collected via Google Form questionnaire which contained items from a work motivation scale with a Likert scale. After being collected, 2 participants with high work motivation and 2 participants with moderate work motivation were interviewed to deepen the work motivation variable. The findings showed that there were 25 teacher participants who had high work motivation and 9 teacher participants who had moderate work motivation. ABSTRAKSekolah Luar Biasa X merupakan sekolah yang menyediakan ruang belajar dan berkembang bagi anak berkebutuhan khusus. SLB X yang telah berdiri lebih dari 25 tahun memiliki beberapa cabang. Tujuan penelitian untuk mendeskripsikan motivasi kerja guru di Sekolah Luar Biasa X. Metode penelitian yang digunakan mixed methods dengan jenis desain quantitative preliminary. Peneliti mengumpulkan data kuantitatif, membuat suatu kuesioner dan mencari partisipan untuk digali lebih lanjut melalui wawancara terkait motivasi kerja. Survei atau kuesioner yang bersifat kuantitatif memberikan gambaran umum, wawancara yang bersifat kualitatif akan memberikan deskripsi lebih lanjut mengenai motivasi kerja. Penelitian ini melibatkan 34 partisipan guru yang terdiri dari 14 laki-laki dan 20 perempuan. Data motivasi kerja dikumpulkan melalui kuesioner google form yang memuat butir dari skala motivasi kerja dengan skala Likert. Setelah dikumpulkan, 2 partisipan dengan motivasi kerja tinggi dan 2 partisipan dengan motivasi kerja sedang, dilakukan diwawancara untuk mendeskripsikan motivasi kerja. Hasil temuan menunjukkan terdapat 25 partisipan guru yang memiliki motivasi kerja tinggi dan 9 partisipan guru yang memiliki motivasi kerja sedang.